Food safety knowledge and personal hygiene towards hygiene practices amongst mobile food handlers in Shah Alam, Selangor / Faridah Hanim Ismail - Ismail, Faridah Hanim (2013)
Rising cost of living encourage people to seek more economical way to spend, and expenses on food become one of the main concern. Other than restaurants, mobile food vendors have become popular as a convenient and low cost ready-to-eat food supplier. Nevertheless, people are aware about eating safe food during their eating out activities. Unfortunately, findings from recent studies have shown rising cases of food borne illnesses where consuming food purchased from mobile food vendors is one of the main sources. In spite of that, people still prefer to buy food from the mobile food vendors due to several reasons; low cost of food, high availability, and changing demands by the urbanization. Ready-to-eat food from mobile food vendors is becoming preferable because people are now having less time to prepare food at home due to busy schedule. Thus, in order to prevent foodbome illnesses and sustain mobile food vendors businesses at the same time, these operators’ knowledge, personal hygiene and the hygiene practices on food safety need to be accessed and improve to provide better services and safe food to consumers. Therefore this study examined food safety knowledge, personal hygiene and the hygiene practices amongst mobile food handlers in Shah Alam, Selangor. Using quantitative approach, self administered questionnaire was distributed to 400 mobile food handlers and only 320 questionnaires were collated. Nine areas in Shah Alam were selected as the contextual setting. All the data were analyzed using Descriptive Statistics and Pearson Correlation to see the relationship between food safety knowledge towards hygiene practices. Most of the mobile food handlers are knowledgeable on food safety (51.4%), while only 3.89% knows about personal hygiene and cross contamination respectively. Food hygiene practices are significantly (p<0.01) related to food handlers safety knowledge. It is suggested that improvement on the equipment and utensil would be beneficial to mobile food handlers. Selection of the business location also needs to take into consideration to avoid foodbome illnesses in the future.